2010
DOI: 10.1002/bit.22646
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive multiplex RNA quantification using capillary electrophoresis‐based single‐strand conformation polymorphism

Abstract: Quantification of RNA provides information crucial for various biological studies, including analysis of mRNA expression and that of microRNAs. Reverse transcription (RT) coupled with real-time polymerase chain reaction (PCR) is known to be the most accurate method for quantifying nucleic acids, and thus represents the state-of-the-art for RNA quantification. However, the use of real-time PCR for RNA quantification is limited to a single target per analytical run because of reductions in quantification power a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
(30 reference statements)
0
1
0
Order By: Relevance
“…PCR products from the adult B. schroederi and one or two positive PCRs per fecal sample were analyzed with the CE-SSCP as described by Park et al [16] and Shin et al [17] . Park et al [16] found that high concentration DNA templates might result in nonlinear correlation between the peak areas of CE-SSCP and DNA amounts.…”
Section: Methodsmentioning
confidence: 99%
“…PCR products from the adult B. schroederi and one or two positive PCRs per fecal sample were analyzed with the CE-SSCP as described by Park et al [16] and Shin et al [17] . Park et al [16] found that high concentration DNA templates might result in nonlinear correlation between the peak areas of CE-SSCP and DNA amounts.…”
Section: Methodsmentioning
confidence: 99%